2016
DOI: 10.5902/1980509821060
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento Inicial De Acácia-Negra Com Vermicompostos De Diferentes Resíduos Agroindustriais

Abstract: RESUMOA utilização de vermicompostos de diferentes resíduos agroindustriais na produção de mudas de acácia-negra pode ser uma alternativa de reutilização de resíduos e aumentar a produção de mudas. Assim, os objetivos deste trabalho foram avaliar o crescimento e a concentração de nutrientes em mudas de acácia-negra, cultivadas em substratos com diferentes vermicompostos de resíduos orgânicos agroindustriais. Instalou-se em casa de vegetação 11 diferentes tratamentos: T1) vermicomposto de esterco bovino (EB); T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 0 publications
0
15
0
6
Order By: Relevance
“…A vermicompostagem resulta em um produto considerado adubo orgânico, podendo substituir a utilização de adubação mineral (Steffen et al, 2011;Antunes et al, 2016).…”
Section: Introductionunclassified
“…A vermicompostagem resulta em um produto considerado adubo orgânico, podendo substituir a utilização de adubação mineral (Steffen et al, 2011;Antunes et al, 2016).…”
Section: Introductionunclassified
“…Potassium is a nutrient that does not participate in organic combinations and participates instead in the structural function, which causes it to be readily released when organic fertilizers are used (Kiehl, 2010;Magro et al, 2010). Antunes et al (2016) evaluated the height of the seedlings in black acacia (Acacia mearnsii) and observed that the best value in this variable was obtained in the substrate with the application of vermicompost with the mixture of bovine manure and food residues, whose value was 22.6% superior to the control treatment. The superiority of the values observed in the stem diameter for the pitomba seedlings in the substrate with the fruit and vegetable residue compound can be explained by the high phosphorus, potassium, calcium, and magnesium contents present in this substrate in relation to the other substrates evaluated, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The values observed for the nitrogen contents are higher than those of the other plant species studied, as described by Barros et al (2013), who worked with different organic substrates in yellow passion fruit seedlings (Passiflora edulis Sims f. Flavicarpa Degene) and showed that the nitrogen accumulation was better in the substrate composed of soil and tanned bovine manure. Reis et al (2015) obtained a value of 16.79 g kg -1 working with Dilodendron bipinnatum Radkl (Sapindaceae); whereas Antunes et al (2016) found values varying between 9.73 and 12.44 g kg -1 using vermicompostos of different agroindustrial residues in black acacia (Acacia mearnsii Wild). The same authors have reported that the concentration of nutrients may be an indication of nutrition because of the different types of nutrient source applied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations